Pengaruh Core Stability Exercise Dengan Pendekatan Bobath Concept Terhadap Keseimbangan Pasien Pasca Stroke - Iqbal, Mohammad, Umi Budi Rahayu, S. Fis., M. Kes (2017)
Aim : this research aim to know therapeutic exercise appplication with Bobath Concept approach combining with Core Stability Exercise to improve balance. Quasi experimental design A-B-A use 2 samples measuring every series at a control grup ar RSU Anwar Medika Sidoarjo. Data analysis with simple descriptive statistic to get obvious image about intervention outcome, using line graphic as an interpretation of treatment and outcome. Based on the grapic shows there is improvement after Core Stability Exercise and New Bobath Concept approach get improvement in 2 items in first week and 2 items in third week. In second week only 1 item get improvement. Conclusion is there is improvement effect in balance by treatment Core Stability Exercise and New Bobath Concept approach. Keywords : The effect of Core Stability Exercise with Bobath Concept approach to the balance of post stroke patiens.